Salon van de Maassteden. (Schiedam : Stedelijk Museum Schiedam, 1982)
van den Akker, Elizabeth ; Andringa, Hans ; Arenas, Maria ; den Arend, Lucien ; Belzer, George ; van Bemmel, Marcelle ; Bergsma, Auke ; Blok, Ernst ; Brans, Joop ; Boogert, Eddie ; Bout, Rien ; Bouw, Cees ; van Dijk, Cor ; Dolieslager, Hans ; Dolz, Dora ; Dumas, Peter ; Eldering, Lies ; etc.
Salon van de Maassteden, Stedelijk Museum Schiedam, 24 april - 30 juni 1982
boek